Psychotropic medication non-adherence and its determinants among people living with mental illnesses in Ethiopia: systematic review and meta-analysis study - Gebresilassie Tadesse; Gebremariam Wulie Geremew; Tekletsadik Tekleslassie Alemayehu; Demis Getachew; Digafe Demelash; Setegn Fentahun (BMC Public Health)
Abstract Background Over half of patients take medications incorrectly, with non-adherence being a significant challenge in managing mental illnesses and to healthcare systems globally. In mental health, non-adherence to psychotropic medications exacerbates symptoms, increases relapse rates, and contributes to treatment resistance, higher hospitalization rates, and mortality. It also places a financial burden on healthcare systems through preventable hospitalizations and prolonged treatments. Understanding the prevalence and determinants of non-adherence is particularly critical in low-resource settings like Ethiopia, where mental health services are underfunded and sociocultural factors influence treatment behaviors. Therefore, this study aimed to estimate the pooled prevalence and determinants of psychotropic medication non-adherence in Ethiopia. Methods Primary articles were sourced from PubMed (Medline), EMBASE, CINAHL, Web of Science, PsycINFO, Google, and Google Scholar. The review included studies reporting the prevalence and determinants of psychotropic medication non-adherence among individuals with mental illness. Data were extracted using Microsoft Excel and analyzed in STATA 14. A random effects model was applied to estimate the pooled prevalence, and subgroup analyses were performed to explore heterogeneity. Publication bias was assessed using Egger’s test and a funnel plot. Results Seventeen studies with 7,097 participants were included. The pooled prevalence of psychotropic medication non-adherence was 43.98% (38.15, 49.81). Subgroup analysis revealed regional variations with prevalence rates of 52.85% in Harari, 52.4% in Amhara, 46.39% in Oromia, 39.8% in Addis Ababa, and 27.42% in Tigray. Significant determinants included negative attitudes toward treatment (OR: 3.69; 95% CI: 2.73–4.99), lack of insight (OR: 3.20; 95% CI: 1.71–5.99), medication side effects (OR: 2.84; 95% CI: 2.05–3.93), perceived stigma (OR: 2.41; 95% CI: 1.87–3.10), substance use (OR: 2.36; 95% CI: 2.02–2.74), and poor social support (OR: 2.30; 95% CI: 1.61–3.29). Conclusions and recommendations This study found that over four in ten people with mental illness were non-adherent to medications. It is recommended to design intervention strategies that address the factors associated with non-adherence to psychotropic medication. Prospero registration CRD42024563343.